Board of Commissioners’ Structure, Ownership Retention, and IPO Underpricing: Evidence from Indonesia - Doddy Setiawan (Etikonomi, 2021)
This research examines how the board of commissioners' structure and ownership retention affect IPO underpricing in Indonesia. In this study, we have examined the following three aspects: the number of board of commissioners, percentage of independent commissioners, and percentage of female commissioners. In total, 186 Indonesian companies that have conducted IPO from 2001 to 2016 were included in this study. This study uses multiple regressions to test the hypothesis. Our findings show that ownership retention has a negative implication on underpricing. Furthermore, the number of board of commissioners and independent commissioners has also been determined to reduce the level of underpricing. However, female commissioners were found to have no significant effect on IPO underpricing; furthermore, it demonstrated no significant effect in reducing the level of underpricing. These results show that higher ownership retention, a smaller number of board members, and a higher percentage of independent commissioners can reduce IPO underpricing. JEL Classification: G30, G32